Performance Analysis On The H. Iksan Pamanukan Road Section Pamanukan District - Subang Regency - Adil Prayitno; Ryan Syahril (Riviera Publishing, 2025)
H.Iksan Road Section Pamanukan is road urban area located in Subang Regency with amount population in 2022 will be 1,624,386 people , increasing increasing amount resident impact on increasing need various activity public Good activity economy , social , education and office , on the section road H. Iksan Pamanukan is areas that are often passed by vehicle motorized , along second side road there is shops , and street vendors so that often happen obstacle high side , and so No direct influential to current Then cross as well as performance on the section road the . Study This aiming For analyze performance section H. Iksan Street Pamanukan . Study This consists of from two stages that is collect secondary data and primary data that is needed , such as amount resident Subang Regency , map location section road H. Iksan Pamanukan , geometric road , traffic volume cross vehicle , speed vehicles and obstacles side . Then analyze it use manual capacity method Indonesian roads in 1997 in particular For road urban . The results of the data analysis are obtained in volume and then cross peak happened in the afternoon of 2223.8 smp / hour with peak weight incident obstacle side amounting to 904.4 incidents /hour, and mark degrees saturation of 0.851, then can be concluded level service road H. Iksan Pamanukan is at level E, where Current No stable , speed sometimes stopped , request Already approach capacity .